Pemberdayaan Masyarakat Pada Program CSR Satu Padu Melalui Budidaya Jamur - Beti Nur Hayati; Andy Yudha Hutama; Ita Puspitasari; Nuril Khatulistiyawati (Ininnawa : Jurnal Pengabdian Masyarakat, 2023)
Since the enactment of Law Number 40 Year 2007 concerning Limited Liability Companies (hereinafter referred to as Law No. 40 of 2007 concerning Limited Liability Companies), the government has mandated that companies must participate in social responsibility. Companies are entities with social responsibilities to their surrounding communities. One way to achieve this is through the implementation of CSR aimed at empowering the community. One such implementation is the One Unified Program carried out by PT Pertamina Patra Niaga Integrated Terminal Surabaya in Jambangan Village, Surabaya City. This Empowerment program is divided into several stages. First, program planning and socialization. Second, program formulation in collaboration with the community. Third, mushroom house development. Fourth, replication and training in mushroom-based food processing. Fifth, marketing of mushroom product results. The results of this activity show that CSR activities, especially community empowerment through mushroom cultivation by PT Pertamina Patra Niaga Integrated Terminal Surabaya, directly and indirectly contribute to community empowerment through economic improvement. The direct economic benefits are evident from the profits generated from the sale of raw mushrooms and various innovations derived from mushroom products. Meanwhile, another benefit of empowerment is the increased capacity, as seen in the improved culinary skills of group members in processing mushroom-based foods.